Hands-on transfer learning with Python : implement advanced deep learning and neural network models using TensorFlow and Keras - Sarkar, Dipanjan; Bali, Raghav; Ghosh, Tamoghna (Packt Publishing, 2018)
The purpose of this book is two-fold, we focus on detailed coverage of deep learning and transfer learning, comparing and contrasting the two with easy-to-follow concepts and examples. The second area of focus is on real-world examples and research problems using TensorFlow, Keras and Python ecosystem with hands-on examples.